2011
DOI: 10.1039/c0nr00887g
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles for the colorimetric and fluorescent detection of ions and small organic molecules

Abstract: In recent years, gold nanoparticles (AuNPs) have drawn considerable research attention in the fields of catalysis, drug delivery, imaging, diagnostics, therapy and biosensors due to their unique optical and electronic properties. In this review, we summarized recent advances in the development of AuNP-based colorimetric and fluorescent assays for ions including cations (such as Hg(2+), Cu(2+), Pb(2+), As(3+), Ca(2+), Al(3+), etc) and anions (such as NO(2)(-), CN(-), PF(6)(-), F(-), I(-), oxoanions), and small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
249
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 394 publications
(253 citation statements)
references
References 141 publications
2
249
0
Order By: Relevance
“…12 In this study, we studied the effects of salts (including NaCl, MgCl 2 , and CaCl 2 ) concentrations on the stability of Au@PEG-F NPs. The concentration of these salts ranged in 0.5−500 mM.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…12 In this study, we studied the effects of salts (including NaCl, MgCl 2 , and CaCl 2 ) concentrations on the stability of Au@PEG-F NPs. The concentration of these salts ranged in 0.5−500 mM.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The smaller nanoparticles also show a higher rate of cellular uptake than larger ones. 7,8 Conventional approaches for preparing drugloaded PLGA nanoparticles include emulsion-solvent evaporation, nanoprecipitation and polymerization. 9 Among these techniques, nanoprecipitation can easily produce small PLGA nanoparticles (<100 nm) by dissolving the polymer and drug in organic solution followed by adding aqueous solution.…”
mentioning
confidence: 99%
“…It has been reported that H 2 O 2 can directly etch gold nanorods in the presence of CTAB. 38,39 Most recently, Ni and co-workers also proposed and certified a Br 3 − mediated etching of GNRs by H 2 O 2 . 40 However, in our system, 0.2 mM H 2 O 2 induced a very tiny change of LSPR of GNRs with the presence of 10 mM CTAB ( Figure S1), which is also consistent with the previous results that H 2 O 2 below 10 mM led to negligible oxidation of GNRs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The GNRs were synthesized using a modified method by changing the amount of AgNO 3 . 34 (1) Seed Solution: To 7.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%